Assessment of Watershed Carrying Capacity and Land Use Change on Flood Vulnerability Areas in Semarang City - Dewi Liesnoor Setyowati; Satria Adji Wilaksono; Ananto Aji; Muhammad Amin (Universitas Muhammadiyah Surakarta, 2021)
Human behavior can cause watershed problems, in which the use and carrying capacity of the watershed do not correspond. The objectives of this research are to determine the land use conditions and carrying capacity of the watersheds, and to analyze this capacity based on changes in land use and flood vulnerability areas. The research was conducted in five watersheds flowing are in flood-prone areas of Semarang City, namely Babon, Banjir Kanal Timur, Garang, Silandak, and Beringin, with a research area of 48,994.62 Ha. A quantitative analysis approach was used to calculate the land-use change and watershed carrying capacity; the capacity variables included land conditions, water quality, population, water building, and watershed space utilization. The results show that 1) an average of 12.27% of land in each watershed unit has been converted into settlements, with the most extensive conversion being in the Banjir Kanal Timur watershed; 2) the carrying capacity of this watershed got 113 scores, which fell into the poor category; and 3) at the watershed level, the surge in land conversion into settlements correlates with the carrying capacity of the watershed. Conversion of land into settlements is one of the determinants of the carrying capacity of the watershed. If the land use arrangement in the watershed is made with consideration of flood-vulnerability areas, this will be able to reduce watershed damage and reduce the frequency of floods.